Теория и методология зарубежного литературоведения: учеб. пособие / О. Н. Турышева - Турышева Ольга Наумовна (Флинта, 2012)
Экземпляры: ф.4 (20140623) / Инвентарный номер: 55909 / Цена: / Сис.шифр: 83.3(4) / Авт.знак: Т 89 / ГРНТИ: 17.01 / ББК: 83.3(4)я73